Comparison of levels and duration of detection of antibodies to bovine viral diarrhea virus 1, bovine viral diarrhea virus 2, bovine respiratory syncytial virus, bovine herpesvirus 1, and bovine parainfluenza virus 3 in calves fed maternal colostrum or a colostrum-replacement product - Chamorro, Manuel F. (Canadian Veterinary Medical Association, 2014)
Colostrum-replacement products are an alternative to provide passive immunity to neonatal calves; however, their ability to provide adequate levels of antibodies recognizing respiratory viruses has not been described. The objective of this study was to compare the serum levels of IgG at 2 d of age and the duration of detection of antibodies to bovine viral diarrhea virus 1 (BVDV-1), bovine viral diarrhea virus 2 (BVDV-2), bovine respiratory syncytial virus (BRSV), bovine herpesvirus 1 (BHV-1), and bovine parainfluenza virus 3 (BPIV-3) in calves fed maternal colostrum (MC) or a colostrum replacement (CR) at birth. Forty newborn male Holstein calves were assigned to the CR or the MC group. Group CR (n = 20) received 2 packets of colostrum replacement (100 g of IgG per 470-g packet), while group MC (n = 20) received 3.8 L of maternal colostrum. Blood samples for detection of IgG and virus antibodies were collected from each calf at birth, at 2 and 7 d, and monthly until the calves became seronegative. Calves in the MC group had greater IgG concentrations at 2 d of age. The apparent efficiency of absorption of IgG was greater in the MC group than in the CR group, although the difference was not significant. Calves in the CR group had greater concentrations of BVDV neutralizing antibodies during the first 4 mo of life. The levels of antibodies to BRSV, BHV-1, and BPIV-3 were similar in the 2 groups. The mean time to seronegativity was similar for each virus in the 2 groups; however, greater variation was observed in the antibody levels and in the duration of detection of immunity in the MC group than in the CR group. Thus, the CR product provided calves with more uniform levels and duration of antibodies to common bovine respiratory viruses.